Erosion Prediction Based on Terrestris Survey and RUSLE Method (Revised Universal Soil Loss Equation) in Precet Forest Park, Wagir, Malang - Irawan, Listyo Yudha; Wahyu, Hyundra Zakiya Putri; Firdausa, Ayunda Laras; Wijaya, Andhika Ananda; Azizah, Vischawafiq; Prasetyo, Widodo Eko (Geosfera Indonesia, 2024)
Erosion was a process that led to decreased land productivity and soil layer depletion. Four factors affected erosion, including erosivity, erodibility, slope and land cover. This study aimed to assess erosion predictions based on the results of field measurements or terrestrial surveys and the RUSLE method. Precet Forest Park was the location of the research facility. Erosion prediction was conducted by measuring slopes using Total Station. The RUSLE technique with five variables was used to calculate erosion values. These factors included the slope factor (LS), plant management index and ground cover vegetation (C), soil erodibility (K), rain erosion (R), and soil conservation measures (P). The calculation results indicated that the erosivity value (R) was 254.5, the K value was 0.46, the average LS value is was 8.39, the C value was 0.1, and the P value  was 0.9. Calculations using the RUSLE method yielded an average value of the amount of eroded soil in Precet Forest Park of 86.37 tons/ha/year with a soil solum depth of >90 cm. Based on the erosion classification, the grade was classified as class II (Medium). In general, erosion was categorized as high to very high in the middle slope areas of the mountain. This was due to land cover characterised by thick vegetation. In addition, the soil management practices also reduced the value of erosion in Precet Forest Park.